Carta de Antonio R. Barceló a Luis Muñoz Marín - Todd, Roberto H.; Barceló, Antonio R.; Muñoz Marín, Luis (My University, 1935)
Barceló explica su posición ante la situación del Partido Liberal Puertorriqueño.
Keywords: Partido Liberal Puertorriqueño; Barceló, Antonio R., 1868-1938; Martínez Nadal, Rafael, 1877-1941; Muñoz Marín, Luis, 1898-1980